Civic education of students in the conditions of digitalization and informatization of the education system - Mikhail Vasilievich Nicolaev (Вестник Майкопского государственного технологического университета)
Nowadays the preconditions for the upbringing of the younger generation in the context of the digitalization of society have emerged. This means that changes are taking place in the social, economic and political spheres of life, which entails changes in the methods of teaching and upbringing of the younger generation. The active use of digital technologies in civic education of students creates a high-tech living environment, which leads to the education of competent and competitive digital citizens. In these conditions, the possibilities of education and upbringing of students are expanding, taking into account individual characteristics. The aforementioned emphasizes the relevance of the problem of informatization of society and the introduction of information technologies in the process of civic education of students. The research problem lies in the informatization of society and the widespread use of information systems in the process of civic education of the younger generation. The purpose of the research is to identify topical issues of civic education in the educational process of an educational institution in the context of digitalization and informatization of society. The research methods used are analysis, synthesis, induction, deduction, generalization. The research results: a generalized definition of the concept of civic education in the context of digitalization has been presented; the ways of using multimedia technologies in the educational process have been shown; telecommunication projects for solving problems of civic education and social and psychological attitudes of the younger generation have been described. Key conclusions: information systems have a high educational potential, as they ensure the availability and quality of the formation of civic values among students at a distance; Internet resources can be the means of civic education; educational work, in the context of the digitalization of society, is a technological process; education of digital citizens requires appropriate pedagogical tools; multimedia technologies allow to instill in students the civic values of education.